Costing practices: The case of hotel industry in Malaysia - Mohamed, Rapiah; Alwi, Kasumalinda; Tan, Chee Yu (Universiti Utara Malaysia, 2005)
With escalating competition in the hotel industry, the hotel management should put more emphasis on management and accounting techniques such as cost system design to create and sustain competitive advantage. This study investigates the practice of costing method adopted by hotel industry in Malaysia. The survey method is used to achieve the objective of the study and 274 hotels were selected as sample. This study employs descriptive analysis to explain the costing practice. The results of the study indicate that most of the hoteliers are still practicing the traditional method of costing. However, activity based costing has been practiced by a few hoteliers and a few more are looking forward to implement it in the future. Operation costing and job order costing are the most preferable costing method used in hotel industry. For overhead costs allocation, this study found that the majority of hoteliers use activity allocation and multiple allocation method and direct labor is reported as the most preferable allocation base.